2021
DOI: 10.3390/jrfm14030090
|View full text |Cite
|
Sign up to set email alerts
|

Causal Links between Trade Openness and Foreign Direct Investment in Romania

Abstract: In this increasingly globalized era, foreign direct investments are considered to be one of the most important sources of external financing for all countries. This paper investigates the causal relationship between trade openness and foreign direct investment (FDI) inflows in Romania during the period 1997–2019. Throughout this study, Trade Openness is the main independent variable, and Gross Domestic Product (GDP), Real Effective Exchange Rate (EXR), Inflation (INF), and Education (EDU) act as control variab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
19
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(30 citation statements)
references
References 30 publications
(42 reference statements)
7
19
0
4
Order By: Relevance
“…For instance, Saleem et al (2018) found bidirectional causality between labor cost and FDI in China. Lastly, this paper reveals bidirectional causality between FDI and TO in Bangladesh, which is consistent with Rathnayaka Mudiyanselage et al (2021) in the case of Romania but different from Saleem et al (2020) in the case of Bangladesh. Moreover, "TO causes FDI" and "FDI causes TO" both are natural relationships.…”
Section: Analysis Of Var Results and Granger Causality Testsupporting
confidence: 80%
“…For instance, Saleem et al (2018) found bidirectional causality between labor cost and FDI in China. Lastly, this paper reveals bidirectional causality between FDI and TO in Bangladesh, which is consistent with Rathnayaka Mudiyanselage et al (2021) in the case of Romania but different from Saleem et al (2020) in the case of Bangladesh. Moreover, "TO causes FDI" and "FDI causes TO" both are natural relationships.…”
Section: Analysis Of Var Results and Granger Causality Testsupporting
confidence: 80%
“…It confirms that inflation cannot account for major variations in FDI inflows to Sri Lanka throughout the years. This result support to the findings of [71][72][73][74].Surprisingly, the results in our study demonstrate no substantial association between FDI inflows and human capital, despite the fact that the function of human capital in attracting FDI is well recognized in the literature [31,39,50,78,83,86]. Finally, the R squared value associated the selected long run model is 0.871925.…”
Section: Resultssupporting
confidence: 89%
“…According to economic and investment theories, inflation encourages FDI through local and global shocks and influences other macroeconomic factors [43]. In most empirical investigations [3,7,43,57,69,70] there was a negative association between inflation and FDI inflows, while other studies [71][72][73][74] found no significant impact of inflation rate on FDI inflows. Human capital: Theoretical literature has reflected that human capital in host nations is a determinant of foreign investment in emerging countries.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Impact of trade openness on environmental quality Trade openness has a connection and will influence FDI (Burange et al, 2019;Djulius, 2017;Makoni, 2018;Rakshit, 2022;Rathnayaka Mudiyanselage et al, 2021). Kumari et al (2021) found that there was a long term causal connection between FDI, trade openness and economic growth in India and FDI and trade openness influenced both ways.…”
Section: Literature Reviewmentioning
confidence: 99%